4 - Denial and violence:Paradoxes in men’s perspectives to premarital sex and pregnancy in Rural Zimbabwe - Jeremiah Chikovore; Gunilla Lindmark; Beth Maina Ahlberg (African Sociological Review, 2004)
This paper describes the perspectives of men on premarital sex and pregnancy in rural Zimbabwe. It is based on data collected using three qualitative methods including focus group discussions and individual interviews among men and women, and self-generated questions and statements among school youth. The paper illuminates the paradoxes of denial and violence implicit in the way men speak: as relatives on the one hand and as and as partners on the other regarding pregnancy in girls.The men say they react violently to premarital pregnancy, but neither do they tolerate sexual activity, or allow contraceptive information or service for unmarried daughters and sisters, even though their accounts paradoxically suggest that sexual abuse of young girls is rampant. Despite denying them preventive service and information, men speaking as partners expect girls to have knowledge about sexuality, the menstrual cycle and pregnancy. They blame their girlfriends for getting pregnant, despite indications from the accounts of the girls that it is male partners who pressure the girls into unprotected sexual activity. In such circumstances, the girls say the pregnancy may translate into unsafe, induced abortion. These are complexities at the micro-level that need to be understood for any meaningful programme to improve adolescent sexual and reproductive health.